The social network among the elderly and its relationship with quality of life - Bahramnezhad, Fatemeh (Electron Physician, 2017)
INTRODUCTION: Attention to the needs of the elderly is a social necessity, and it seems that evaluating the social network and quality of life of the elderly can be useful in a better understanding of their needs. This study was performed to determine the relationship between the social network and the quality of life of the elderly in the city of Bojnoord in Iran. METHODS: In this cross-sectional study, 201 elderly people aged 60 years or more were selected by continuous and consecutive sampling method in Bojnoord, Iran in 2014. Data were collected using demographic questionnaire, Lubben social network scale and LEIPAD elderly quality of life questionnaire. Data were analyzed by SPSS 16 and using descriptive statistics and independent-samples t-test, ANOVA and Pearson product-moment coefficient. RESULTS: The results showed that 30.3% of elderly people studied, were subjected to a high risk of isolation. The highest mean in social network dimensions was in the family (19.68%), friends (12.01%) and the neighbors (9.90%), respectively. The mean score for quality of life of the elderly was as moderate to high (63.90±13.73), and among the quality of life dimensions, the highest mean was related to the self-care dimension (15.59%), and the lowest mean was related to the sexual functioning dimension (1.53%). The findings suggested a positive and significant relationship between social network and quality of life in the elderly who were studied (p<0.000, r=0.468). CONCLUSION: This study was a step toward understanding the social network status and quality of life of the elderly. It is necessary to say that health care professionals, especially nurses, display a significant role in the community to help people in this regard.